Molecular detection and characterisation of feline morbillivirus in Malaysia - Mohd Isa, Nur Hidayah (2019)
Feline morbillivirus (FeMV), a feline virus under the family of Paramyxoviridae was identified in several countries across the world. This virus is the largest morbilliviruses with the size of 16,050 bases and encodes eight non-structural and structural proteins, which are the N, P/V/C, M, F, H and L proteins. Phylogenetic analysis revealed that this virus shared less than 80% nucleotide identities to other known paramyxoviruses. There was also evidence of higher detection of FeMV in kidney tissue compared to other type of samples suggesting the virus is nephrotropic. To date, no study has been conducted in Malaysia to determine the presence as well as to characterise the local FeMV isolates. Therefore, the objectives of this study were to detect and characterise FeMV from domestic cats in Malaysia. Molecular analysis utilising nested RT-PCR assay targeting the L gene of FeMV performed on either urine, blood and/or kidney samples collected from the 208 cats in this study revealed 82 (39.4%) positive cats. From these 82 samples, FeMV RNA were detected from 48 (58.5%) pet cats and 34 (27.0%) shelter cats. FeMV-positive samples were found from 63/124 (50.8%) urine samples and 20/25 (80.0%) kidney samples, while all blood samples 0/96 (0.0%) were negative for FeMV. In this study, a new primer set was developed targeting partial N gene of FeMV by RT-PCR. Partial L and N gene sequencing of the RT-PCR-positive samples showed 85-99% identity to the previously reported FeMV and it is significantly different from all other morbilliviruses. Phylogenetic analyses of the identified Malaysian FeMVs were clustered with other Asia FeMVs. Additionally, randomly selected urine samples were cultured where out of four FeMV positive urine samples, two samples showed CPE which is characterised by cell clumping, cell rounding, detachment, lysis and syncytia formation at day 12. This study is focused on a preliminary investigation of the existence of feline morbillivirus in Malaysia. The detection and molecular characterisation of this virus in domestic cats in Malaysia is important in order to examine the existence and significance of this virus to the feline population.